DON JUAN VICENTE GUTIÉRREZ DE SALAMANCA FERNÁNDEZ DE CÓRDOBA, ARQUITECTO CORDOBES DE LOS SIGLOS XVIII Y XIX - Rivas Carmona, Jesús (Imafronte, 1985)
In the second half of the XVlll century the barroque style of architecture was still firmly established in the old kingdom of Córdoba, especially in folk circles, whereas in the capital city of Córdoba itself and in some of the small villages that had been influenced by the Age of Enlightenment, neoclassicism was beginning to take root. One of these such places was the village of Aguilar de la Frontera, where Don Juan Vicente Gutiérrez de Salamanca was working as an architect. Related by marriage to important noble families, and himself a rich landowner, he embodied the learned prototype of that era with his manifest interest for agriculture and other works of public benefit, especially architecture. He had dedicated himself to the latter since his youth, and before reaching the age of thirty he had already planned the construction of the Clock Tower, in a typically baroque style. However, from this flowery architectural style he eventually evolved into a strict neoclassicist, no doubt due to his being a learned man, as various different noble families from the above mentioned village have testified. Nevertheless his crowning work is that of the Plaza de San José (St. Joseph’s Square) which. possibly inspired by that of Archidona, constitutes one of the finest examples of an octagonal square closed off in accordance whith the French influences that were fashionable in Spain at that time.